The Impact of Rotating Night Shift Work and Daytime Recharge on Cognitive Performance Among Retired Nurses - Gan, Jinghuan; Wang, Xiao-Dan; Shi, Zhihong; Yuan, Junliang; Zhang, Meiyun; Liu, Shuai; Wang, Fei; You, Yong; Jia, Peifei; Feng, Lisha; Xu, Junying; Zhang, Jinhong; et al. (Frontiers in Aging Neuroscience, 2022)
Introduction: The exact relationship between long-term shift work and cognitive impairment (CI) has been poorly understood. The effects of long-term rotating night shift work combining day time recharge (DTR) on cognitive function was investigated. Methods: Amount of 920 retired nurses and 656 retired female teachers ≥ 50 years of age were analyzed. Participants who worked at least once per week 8 hrs at night for more than one year were defined as the shift-work group, and those without a regular night-time shift were the control group. The associations among duration, frequency, and DTR of rotating night shift work, and neuropsychological assessments were ascertained by regression models. Results: Participants with rotating night shift work had significantly higher proportion of MCI, both aMCI (14.4% in 11-20 years [p < 0.05], and 17.8% in > 20 years [p < 0.001]) and naMCI (8.1% in 11-20 years, p < 0.05), as well as dementia (1.5% in 1-10 years, and 11.7% in > 20 years, p < 0.05) compared to controls (8.4% with aMCI, 4.4% with naMCI, and 7.0% with dementia, respectively). There were significant negative relationships between general times of night shift work and scores of MMSE (R Squared = 0.01, p = 0.0014) and MoCA (R Squared = 0.01, p = 0.0054). Participants with ≥ 1 hrs DTR and ≥ 11 years rotating night shift work were about two-fold more likely to experience MCI compared with subjects in the control group, especially with 3–5 hrs (OR: 2.35; 95% CI: 1.49–3.68, p < 0.001). Conclusions: Long-term rotating night shift work was associated with a higher risk of CI, especially aMCI and dementia, and the problem can’t be improved by DTR.